Tongan‐English language contact and kinship terminology. Issue 2 (June 2016) - VÖLKEL, SVENJA
ABSTRACT: '[D]o all humans mean the same things by words that can be used successfully to point to the same thing?' (Leavitt2015 : 51). This study shows that the same words used in different English varieties might not have the same meaning. The typological comparison of standardised English and Tongan kinship terminology reveals that the categorisation is based on different underlying features. While standardised English focuses on the concept of 'core family', Tongan merges 'same‐sex siblings' and emphasises the concept of 'extended family'. The emerging contact phenomenon in Tongan English is the use of English terminology according to Tongan categorisation, that is, a case of semantic transfer.